Spotlight on the Selected New Antimicrobial Innate Immune Peptides Discovered During 2015-2019 - Dang, Xiangli; Wang, Guangshun (Current Topics in Medicinal Chemistry, 2020)
Background: Antibiotic resistance is a global issue and new anti-microbials are required. Introduction: Anti-microbial peptides are important players of host innate immune systems that prevent infections. Due to their ability to eliminate drug-resistant pathogens, AMPs are promising candidates for developing the next generation of anti-microbials. Methods: The anti-microbial peptide database provides a useful tool for searching, predicting, and designing new AMPs. In the period from 2015-2019, 500 new natural peptides have been registered. Results: This article highlights a selected set of new AMP members with interesting properties. Teixobactin is a cell wall inhibiting peptide antibiotic, while darobactin inhibits a chaperone and translocator for outer membrane proteins. Remarkably, cOB1, a sex pheromone from commensal enterococci, restricts the growth of multidrug-resistant Enterococcus faecalis in the gut at a picomolar concentration. A novel proline-rich AMP has been found in the plant Brassica napus. A shrimp peptide MjPen- II comprises three different sequence domains: serine-rich, proline-rich, and cysteine-rich regions. Surprisingly, an amphibian peptide urumin specifically inhibits H1 hemagglutinin-bearing influenza A virus. Defensins are abundant and typically consist of three pairs of intramolecular disulfide bonds. However, rat rattusin dimerizes via forming five pairs of intermolecular disulfide bonds. While human LL-37 can be induced by vitamin D, vitamin A induces the expression of resistin-like molecule alpha (RELMα) in mice. The isolation and characterization of an alternative human cathelicidin peptide, TLN-58, substantiates the concept of one gene multiple peptides. The involvement of a fly AMP nemuri in sleep induction may promote the research on the relationship between sleep and infection control. Conclusion: The functional roles of AMPs continue to grow and the general term “innate immune peptides” becomes useful. These discoveries widen our view on the anti-microbial peptides and may open new opportunities for developing novel peptide therapeutics for different applications.
Keywords: Anti-microbial peptide